2010
DOI: 10.1007/s00268-010-0415-6
|View full text |Cite
|
Sign up to set email alerts
|

Course of Ionized Calcium After Thyroidectomy

Abstract: Measurement of ionized calcium on postoperative days 1 and 2 is sufficient for the evaluation of post-thyroidectomy hypocalcemia. Ionized calcium concentrations <1.03 mmol/l on postoperative day 1 are indicative of the presence of symptoms and the need for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Two patients with a PTH 24h of 10-15 ng/L did not develop hypocalcemia (so-called false positives); such patients have also been previously reported [18,24]. Surprisingly, up to 34 % of the non-Graves' disease patients with a QiPTH 15 C15 ng/L developed transient hypocalcemia (so-called false negatives); this high rate is close to the 40.8 % reported by de Andrade Sousa et al [25]. Actually, the PTH level declined 15 % from baseline in non-Graves' disease patients with a QiPTH 15 C15 ng/L, and even 3 % of our patients with a normal PTH level after a hemithyroidectomy developed transient hypocalcemia (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Two patients with a PTH 24h of 10-15 ng/L did not develop hypocalcemia (so-called false positives); such patients have also been previously reported [18,24]. Surprisingly, up to 34 % of the non-Graves' disease patients with a QiPTH 15 C15 ng/L developed transient hypocalcemia (so-called false negatives); this high rate is close to the 40.8 % reported by de Andrade Sousa et al [25]. Actually, the PTH level declined 15 % from baseline in non-Graves' disease patients with a QiPTH 15 C15 ng/L, and even 3 % of our patients with a normal PTH level after a hemithyroidectomy developed transient hypocalcemia (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Determination of serum calcium and/or the PTH levels at day 1 to discriminate the patients who are truly at risk of hypocalcaemia [12, 13]. This stance avoids unnecessary treatment of patients that will ultimately not develop hypoPTH (24 patients [9%] in our study), but it exposes (at the onset of symptoms) the patients that will really develop hypoPTH (31 patients [12%] in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al (20) consider intact PTH level one hour after surgery to be a sensitive predictor of the risk of developing postoperative symptomatic hypocalcemia. According to other authors, sufficient indication is provided by ionized calcium levels on postoperative days 1 and 2 (21). Given the difficulties involved in identifying factors increasing the risk of hypocalcemia after thyroidectomy, other authors have suggested routinely issuing discharged patients with a prescription for continuous oral calcium, with or without oral vitamin D (22).…”
Section: Discussionmentioning
confidence: 99%